Idiosyncratic risk in the 1990s: Is it an IT story? - Dietrich Domanski (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
This paper examines trends in idiosyncratic risk in different `new economy' and `old economy' industries, and explores whether these developments can be attributed to the use of IT. A CAPM-based decomposition of equity returns is employed to estimate idiosyncratic risk. The results provide evidence of an increase in idiosyncratic risk in the 1990s. A substantial part reflects high volatility of firms in the IT sector, and in particular that of new IT firms. However, it is not clear whether the increase in idiosyncratic risk results from changes in the risk perception of financial markets or from new ways of firm organization', production and competition related to IT. The jump in volatility in 1998 supports the view that the perception of risk by equity investors has changed. The positive relation between the share of intangible assets (as a proxy for IT-related changes) and the increase in firm-specific risk in the 1990s is consistent with the view that IT increases the uncertainty with respect to firm valuation, particularly if associated with a fundamental change in the business model. – ICT ; firm organization ; idiosyncratic risk ; equity market volatility ; intangible assets
Keywords: D23; G12; G5; 330